2022
DOI: 10.1021/acs.est.2c07399
|View full text |Cite
|
Sign up to set email alerts
|

Roles of MnO2 Colloids and Mn(III) during the Oxidation of Organic Contaminants by Permanganate

Abstract: Although intermediate manganese species can be generated during the reactions of permanganate (Mn(VII)) with organic pollutants in water, the role of the in situ generated MnO2 colloids in the Mn(VII) oxidation process remained controversial and the contribution of Mn(III) was largely neglected. This study showed that the apparent second-order rate constants (k app) of Mn(VII) oxidation of methyl phenyl sulfoxide and carbamazepine remained constant with time. However, the degradation of four selected phenolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 35 publications
2
25
1
Order By: Relevance
“…Previous research has revealed the critical role of Mn­(III) aq for phenol removal by Mn­(VII), especially under acidic conditions . Therefore, soluble Mn­(III) aq is another possible candidate for the rapid degradation of phenol in the HCO 3 – /Mn­(VII) process.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…Previous research has revealed the critical role of Mn­(III) aq for phenol removal by Mn­(VII), especially under acidic conditions . Therefore, soluble Mn­(III) aq is another possible candidate for the rapid degradation of phenol in the HCO 3 – /Mn­(VII) process.…”
Section: Resultscontrasting
confidence: 99%
“…MnO 2 colloids formed from Mn­(VII) decomposition generally exhibit excellent reactivity in removing contaminates through oxidation and/or catalytic processes. , Figure S13 unravels that phenol degradation by ectopically prepared MnO 2 colloids cannot be accelerated by HCO 3 – , suggesting that the enhanced removal of phenol is not associated with an increase in the oxidation ability of MnO 2 . Moreover, a previous study demonstrated the limited role of MnO 2 in phenol removal at pH 3.0–8.0 . Therefore, MnO 2 oxidation is likely to play a minor role in the HCO 3 – /Mn­(VII) system.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations